2015
DOI: 10.1095/biolreprod.115.128868
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic Profiling of Bovine Endometrial Immune Response In Vitro. I. Effect of Lipopolysaccharide on Innate Immunity1

Abstract: The dysregulation of endometrial immune response to bacterial lipopolysaccharide (LPS) has been implicated in uterine disease and infertility in the postpartum dairy cow, although the mechanisms are not clear. Here, we investigated whole-transcriptomic gene expression in primary cultures of mixed bovine epithelial and stromal endometrial cells. Cultures were exposed to LPS for 6 h, and cellular response was measured by bovine microarray. Approximately 30% of the 1006 genes altered by LPS were classified as bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 61 publications
6
57
0
Order By: Relevance
“…in agreement with previous findings [18] [20], as well as the cytosolic PRRs IFIH1 [21], DDX58 and LRRFIP1. These receptors have important roles in detecting both extracellular and intracellular pathogens during innate immunity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…in agreement with previous findings [18] [20], as well as the cytosolic PRRs IFIH1 [21], DDX58 and LRRFIP1. These receptors have important roles in detecting both extracellular and intracellular pathogens during innate immunity.…”
Section: Discussionsupporting
confidence: 94%
“…We previously showed peak expression of TNF at 1 h after treatment of BEESC with LPS although the peak response to IL1B was at 6 h [20] so it is possible that a peak cytokine response to poly(dA:dT) had occurred earlier than the first time of assessment. These key inflammatory cytokines are an important component of the early innate immune defence [21] and also serve as a crucial link in the development of an adaptive immune response [33]. TLR7/8 agonists also up-regulated many cytokine genes and proteins in human DCs [35].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of an infectious agent and inflammatory mediators on the gene expression and cytokine production of endometrial cells, the endometrial epithelial cells (bEEL, seeded at 35 000 cells per well) and stromal (bCSC, seeded at 8000 cells per well) were cultured in a 24‐well culture plates (Corning Costar) supplemented with RPMI media containing bacterial lipopolysaccharide (LPS, 1 μ g/mL; O111:B4; catalogue number L2630; Sigma‐Aldrich, St. Louis, MO, USA), bovine IL‐1 β (10 ng/mL; catalogue number RBOIL1BI; Thermo Scientific; Frederick, MD, USA), bovine TNF α (50 ng/mL; catalogue number RPB‐341; IBI Scientific, Peosta, IA, USA) or untreated cells (vehicle control) for 6 h and 24 h. The time of 6 h was chosen based on time‐course studies in endometrium which previously had shown to induces changes in inflammatory genes (e.g., CXCL8/IL8, IL1B, IL6 and/or fatty acid cyclooxygenase‐2) that peaked by 6 h following the treatment with LPS (Oguejiofor et al. ; Swangchan‐Uthai et al. ), IL‐1 β (Huang et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Oguejiofor et al. ; Swangchan‐Uthai et al. ) have focused on the characterization of the inflammatory response triggered by infectious agents.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to mastitis, there is evidence for the involvement of selectins in all of these processes. Both SELP and SELL are significantly upregulated in endometrial cells stimulated with the bacterial product lipopolysaccharide (LPS) (Oguejiofor et al, 2015). SELP is also crucial for the migration of PMN into the bovine corpus luteum during luteolysis (Shirasuna et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%